Discussion method accuracy in Islamic higher education: the influence of gender and teaching duration - Syahraini Tambak; Hamzah Hamzah; M. Yusuf Ahmad; Erma Linda Siregar; Desi Sukenti; Mashitah Sabdin; Ratu Bai Rohimah (Jurnal Cakrawala Pendidikan, 2022)
Discussion method are increasingly popular in the learning, but in terms of its accuracy, mixed results are reported without clear reasons. This research aims to explore the impact of gender and teaching duration on discussion method accuracy in Islamic higher education. To evaluate the accuracy of the use of the discussion method, lecturer's teaching duration and gender, a quantitative study with a correlation approach was used. A research project, which deals with the use of discussion methods in lectures using questionnaires, was carried out in two faculties at two universities. Data were collected from 175 lecturers involved in this research. The analysis is differentiated based on the gender and level of teaching duration of lecturers in the competencies being assessed. The results show that the accuracy of the use of the discussion method is low and is related to the gender of the lecturer, that males perceive themselves to be higher in the use of the discussion method than females, and that even using method analysis with methods and implementation in the classroom. Lecturers who teach more than 30 years tend to have higher accuracy in using the discussion method than those with lesser tenure. The findings of this study have implications for the development of "the use of discussion methods in higher education" and it is necessary to examine the reasons behind this difference and to look for steps to improve the accuracy of the use of the discussion method.